2020
DOI: 10.1007/s11069-020-04037-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk interdependency, social norms, and wildfire mitigation: a choice experiment

Abstract: Wildfire presents a growing threat across the American West. We conducted an online choice experiment in Western Colorado to assess how social interactions affect wildfire mitigation decisions through two distinct pathways: risk interdependency (neighbors' conditions affect perceived wildfire risk) and social norms (neighbors' actions affect perceptions of appropriate mitigation choices). In contrast to key observational studies, we find that participants are less likely to choose to mitigate when they have mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The attributes of mitigation measures (such as costs and perceived efficacy) also play a key role in homeowner decisions (Winter and Fried, 2000;McCaffrey, 2008;Collins, 2009). In addition to the characteristics of homeowners, communities, and mitigation measures, spillover effect (normally termed as neighbor decisions) is also identified as one of the main factors affecting mitigation decisions given that wildfire risk is interdependent (Shafran, 2008;Shafran, 2010;Taylor, 2019;Dickinson et al, 2020). If a structure ignites and burns due to flame or firebrand, the burning structure could become a new source of firebrand generation and threaten adjacent structures (Suzuki et al 2014).…”
Section: Proactive Action 1: Individual-level Risk Reduction Actionsmentioning
confidence: 99%
“…The attributes of mitigation measures (such as costs and perceived efficacy) also play a key role in homeowner decisions (Winter and Fried, 2000;McCaffrey, 2008;Collins, 2009). In addition to the characteristics of homeowners, communities, and mitigation measures, spillover effect (normally termed as neighbor decisions) is also identified as one of the main factors affecting mitigation decisions given that wildfire risk is interdependent (Shafran, 2008;Shafran, 2010;Taylor, 2019;Dickinson et al, 2020). If a structure ignites and burns due to flame or firebrand, the burning structure could become a new source of firebrand generation and threaten adjacent structures (Suzuki et al 2014).…”
Section: Proactive Action 1: Individual-level Risk Reduction Actionsmentioning
confidence: 99%
“…This finding is somewhat surprising because a large body of scholarship finds that descriptive norms messages effectively motivate desired behavioral change in nondisaster contexts, such as smoking cessation and tax compliance (Bicchieri & Dimant, 2019;Goldstein et al, 2007;Hallsworth et al, 2017). Our experiments add to the growing evidence that descriptive norms messages are not effective in the disaster context (Dickinson et al, 2020;Mol et al, 2021;Vinnell et al, 2019) compared to the minimal evidence that finds these messages to be effective in the disaster context (Howe et al, 2018).…”
Section: Descriptive Social Norms Messagesmentioning
confidence: 69%
“…Injunctive norms are either the rewards for aligning with others or the punishment for not aligning with others (Cialdini et al, 2006;Hallsworth et al, 2017). Only a few experimental studies have tested social norms messages in disaster preparedness contexts, such as earthquakes and wildfires (e.g., Dickinson et al, 2020;Howe et al, 2018;Vinnell et al, 2019), which can inform the design of messages for risk mitigation in hurricane and flood contexts. Only one study in a flood preparedness context has tested descriptive social norms (Mol et al, 2021), although floods are one of the most common disasters in the United States.…”
Section: Social Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have found social norms, sense of community, and emotional connection to a place (or “place attachment”) to be associated with behavioral adaptation to climate change (van Valkengoed and Steg 2019 ; Howe et al 2021 ) and wildfire risk mitigation and resilience (Prior and Eriksen 2013 ; McCaffrey 2015 ; Howe et al 2018 ). Wildfire mitigation activities also often occur in a social context, where friends and neighbors are reported to influence behavior (Brenkert-Smith et al 2012 , 2013 ; Dickinson et al 2015 , 2020 ) and mitigation is more likely on properties with mitigated neighbors (Shafran 2008 ; Schulte and Miller 2010 ; Warziniack et al 2019 ). Despite this evidence linking social norms and sense of community with wildfire mitigation, we are not aware of any studies that identify the causal effect of highlighting social benefits on observed homeowner behavior.…”
Section: Introductionmentioning
confidence: 99%